Laparoscopy in the evaluation of impalpable testes and its short-term outcomes: A 7 years' experience - Rajarshi Kumar; Kartik Chandra Mandal; Pankaj Halder; Md. Hadiuzzaman; Madhumita Mukhopadhyay; Biswanath Mukhopadhyay (Journal of Indian Association of Pediatric Surgeons, 2017)
Aims: The aim of this study is to report and analyze results of laparoscopy in impalpable testes performed between 2009 and 2016 and its short-term outcomes. Materials and Methods: Demographic data, laterality, laparoscopic findings, operative time, procedure, hospital stay, complications, and follow-up data of 76 patients with 79 impalpable testes from 2009 to 2016 were retrospectively collected and analyzed. Successful outcome was defined as maintenance of intrascrotal position with no atrophy at a follow-up of at least 6 months. Results: Impalpable testes constituted 24% of undescended testes in our series. Mean age was 3.9 years. Forty-two patients had left-sided, 31 right-sided, and three bilateral impalpable testes. Of the 79 clinically impalpable testes, on laparoscopy, 3 were vanishing testes, 52 were intra-abdominal (6 high-lying and 46 low-lying), 18 canalicular and 6 nubbin testes. Ultimately, 52 underwent laparoscopic orchiopexy: 46 single-staged orchiopexy and 6 two-staged Fowler–Stephens procedure. Mean operating time was 77 min. Complications were few and mostly minor. Eleven patients were lost in follow-up. On a mean follow-up of 23 months, one testis that underwent single-staged laparoscopic orchiopexy atrophied whereas good size and intrascrotal position were maintained in the rest. Conclusions: Laparoscopy in impalpable testes was safe, feasible, and effective. Overall outcome was good which was obtained by minimal use of electrocautery, dissection with wide strip of peritoneum and extensive retroperitoneal dissection for mobilization. There is a need for wide reporting of cases from high-volume pediatric surgery centers in India.